Penguatan Sradha dan Bhakti Melalui Pembelajaran Berdiferensiasi pada Pendidikan Agama Hindu di SMAN 1 Abiansemal - Adiatmika, I Kadek; Suwindia, I Gede; Miarta Putra, I Nyoman (Jayapangus Press, 2025)
The declining internalization of Hindu spiritual values, such as sradha (faith) and bhakti (devotion), among Hindu students has raised concerns in the field of education, particularly in Hindu Religious Education. This study aims to explore the implementation of differentiated instruction as a strategy to strengthen sradha and bhakti values at SMAN 1 Abiansemal. Using a descriptive qualitative approach and a case study method, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that differentiated instruction through content, process, and product differentiation effectively accommodates students’ diverse readiness levels, interests, and learning styles. This strategy fosters active engagement in spiritual practices such as daily prayer, participation in religious activities, mutual cooperation, and acts of compassion. The approach also strengthens students’ religious behavior, ethical conduct, and social awareness, while enhancing their moral resilience against the negative influences of modernity. In conclusion, differentiated instruction proves to be a transformative pedagogical approach that not only conveys religious teachings cognitively but also instills them in concrete behavior, making it a relevant strategy for character building based on Hindu values in the contemporary era.